2007
DOI: 10.1038/sj.bmt.1705852
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of patients with AML and MDS who relapse or progress after reduced intensity allogeneic hematopoietic cell transplantation

Abstract: We describe treatment, outcomes and prognostic factors for patients who relapse following transplantation with a reduced intensity conditioning regimen. Seventy consecutive patients with high-risk myeloid malignancies underwent transplant and 25 (36%) relapsed, a median of 120 days later. The median percentage of bone marrow blasts at relapse was 24, the median donor chimerism was 73% and new karyotypic abnormalities occurred in 8 out of 20 (40%) evaluable patients. Twenty-one patients (84%) received aggressiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
59
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 23 publications
5
59
0
1
Order By: Relevance
“…AZA administration and toxicity AZA was administered for a median of three cycles (range, [1][2][3][4][5][6][7][8][9][10][11][12], at a dose of 75 mg/m 2 per day for 7 days every 4 weeks for the majority of the patients (92%). AZA dose was reduced to 60 mg/m 2 per day (two patients) for 7 days according to the attending physician because of fear of toxicity.…”
Section: Patient Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…AZA administration and toxicity AZA was administered for a median of three cycles (range, [1][2][3][4][5][6][7][8][9][10][11][12], at a dose of 75 mg/m 2 per day for 7 days every 4 weeks for the majority of the patients (92%). AZA dose was reduced to 60 mg/m 2 per day (two patients) for 7 days according to the attending physician because of fear of toxicity.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…1,2 Reductions of immunosuppressive therapy, chemotherapy with or without infusion of DLI or second allo-HSCT are regularly proposed, but results remain disappointing. [3][4][5] Azacitidine (AZA), a DNA-hypomethylating agent with a relatively low toxicity profile, emerged in the recent years as an attractive treatment modality in patients with myeloid malignancies who are not eligible to intensive chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] In HSCT2, most published studies have focussed on the effect of a second transplant from the original donor. 3,7 Nevertheless, change to another donor for HSCT2 is frequently considered to increase the efficacy of a putative GvL reaction. However, the impact of donor change on outcome is unclear, and available data are limited.…”
Section: Introductionmentioning
confidence: 99%
“…However, the therapeutic options for patients who relapse after transplantation are limited. 1 Attempts to maximize the GVL effects by donor lymphocyte infusion have been generally unsuccessful for restoration of a CR. 2 Trials of donor lymphocyte infusion in combination with chemotherapy have shown increased response rates, but the long-term survival of relapsed patients is low.…”
mentioning
confidence: 99%